Design and Build a Telegram – Based Infusion Droplet Control and Monitoring System - Syahri Muharom; Adjie Ramadhan; Aloysius Gonzaga Kristianto Juje (Universitas Muhammadiyah Sidoarjo, 2022)
Infusion is an important part of the process of care and healing of patients who are in the hospital, however, the errors often occur in setting the drip or replacing the infusion that has run out, this can cause the patient to die. From these problems, the researcher has an idea by creating a system that can monitor and control the infusion, so that later it can give warnings to nurses based on Telegram. Several sensors are used for the designed system, including load cell, load cell sends data on the weight of infusion fluids to Arduino, then Arduino sends weight information to Telegram to be monitored, infusion drip control system is carried out using servo and optocoupler sensors. From the tests carried out, the servo and optocoupler systems can adjust the infusion drops according to the patient's needs based on orders from the telegram, with an average error of 1.3%, and the system can provide information to the telegram to identify that the infusion fluid is almost empty. From this study, it is expected that the system can assist nurses in monitoring the availability of infusion fluids in patients and can control infusion drops based on patient needs.